Ação e percepção nos processos comunicacionais do corpo em formação - Saito, Cecília Noriko Ito (2007)
The proposal of this thesis is to investigate subjects tided to primordial organizations of communications process of the body in formation, made from the body media theory. In this theoretical investigation, which relates Communications Theory Studies to Cognitive Science Studies, the thesis analyzes and assists the democratic school procedures through experiences that are being made by Lumiar Institute in São Paulo (SP). Among its subjects, the most evident is socialization without ones subjection, in opposite to disciplinary devices, together to autonomy and resistance (Singer, 1997). Lumiar School proposal in Brazil is being internationally recognized, being studied by researchers such as those of Zero Project by Harvard University and MIT (Massachusetts Institute of Technology). Links between practical-theoretical Media-Body Project bibliography and implementation participation of Lumiar Institute projects has shown efficiency while it gets up to date and gets more evidence to the links between body communications studies and survival political strategies. By this way, we intend to research a subject, which involves learning processes in children by approaching concepts such as action, perception, movement, cognition and their connections to the embodied cognition research